The Influence of Learning Facilities on Students' Academic Achievement at the International Islamic Boarding School Malang - Asmariyah, Asmariyah; Supriyanto, Achmad; Sobri, Ahmad Yusuf (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2024)
Abstract: This research aims to describe the level of achievement of learning facility conditions and student learning achievement conditions as well as analyzing the influence of learning facilities on student learning achievement at International Islamic Boarding High School in Malang. This research was conducted on 11th class students at International Islamic Boarding High School level in Malang with a total of 150. The sample in this research consisted of 50 students using a random sampling approach. This research analysis uses a quantitative approach with the SPSS analysis method. Data was collected using a questionnaire research instrument. Then, the data was analyzed using a simple linear regression test. The results of this research are (1) the overall achievement of the independent variable for learning facilities at International Islamic Boarding High School level in Malang is in the high category with an average percentage of 76%; (2) the average achievement of student learning achievement variables reaches the high category with a percentage of 75%; (3) learning facilities have a positive and significant effect on student learning achievement. The correlation coefficient is 82% so the relationship between the two variables is very strong. The limitation of this research is that the proposed model was only tested on students at 3 International Islamic Boarding Schools for high school level in Malang out of a total of 5 schools in Malang. The theoretical implication in this research is that the findings from this research provide very valuable insights for the development of theory and practice related to learning facilities. Keywords: Learning Facilities; Student Learning Achievement; International Islamic Boarding School